The Role of Mediation in Resolving Divorce Cases Due to Physical Incapacity in Indonesian Sharia Courts: Banda Aceh Case Study - Eko Susanto; Melati Andini (Indonesian Journal of Islamic Law, 2023)
This research examines the role of mediation in resolving divorce cases due to physical incapacity such as impotence at the Banda Aceh Sharia Court. With a qualitative approach and case study, this research explores the effectiveness of mediation supported by medical assessment in managing marital conflict. Data was collected through in-depth interviews, participant observation, and document analysis. The research results show that mediation is effective in reducing divorce rates and helping couples overcome impotence problems with appropriate therapy, while reducing social and psychological stigma. This research recommends integrating medical evaluation in mediation and increasing the capacity of mediators, emphasizing the importance of a multidisciplinary approach in mediation to support family well-being and integrity in Islamic family law.